An Epidemiological Review: Double Burden of Malnutrition and Pediatric Comorbidities - Rinawati; Imanullah Akbar Izza Patria; Thontowi Djauhari Nur Subchi; Miftha Churochman (Universitas Muhammadiyah Malang, 2025)
Background: The Double Burden of Nutrition (DBGH) is a public health issue in urban areas of Indonesia. Hospitals are in a unique position to assess the clinical effects of DBGH. However, there are strong suspicions that medical records in hospitals significantly underreport this information. This situation hides the full extent of the problem, which then hinders the proper allocation of resourcesObjectives: T(1) to describe the epidemiological features of pediatric patients with DBGH (Malnutrition/E40-E46 and Obesity/E66) at Muhammadiyah General Hospital Malang (RSUMM) from 2019 to 2025, including diagnosed prevalence, age distribution, and sex; (2) to critically evaluate the diagnosed prevalence (N=1,092) by comparing it to community prevalence, considering the possibility of under-reporting; and (3) to analyze the patterns of comorbidities in the cases that were successfully recorded.Methods: This study used a quantitative, descriptive epidemiological design, specifically a cross-sectional approach. Data were gathered from the electronic medical records of pediatric patients, aged 0-18 years, who had been diagnosed with malnutrition (ICD-10 codes E40-E46) or obesity (E66) at RSUMM between January 1, 2019, and December 31, 2025. This process yielded a total sample size (N) of 1,092 cases.Results During the study, we found 1,092 cases of BGG in the medical records. Of the total, 671 cases (61.4%) were classified as Malnutrition (E40-E46), while 421 cases (38.6%) were classified as Obesity (E66). The highest rate of diagnosed cases was found in the 0-5 age group, which had a rate of 65.9%. Although the 1,092 cases seem substantial and are increasing, a critical examination reveals that this number is considerably lower than estimates of the community-level burden of BGG (e.g., national stunting prevalence in 2023 SKI >20%), suggesting considerable under-reporting. Analysis of the data shows a significant increase in BGG cases, going from 100 cases in 2019 to 250 cases by 2024. Acute Respiratory Infections (ARI/Pneumonia) and Diarrhea (Gastroenteritis) are the most common health problems seen with BGG.